1996
DOI: 10.1029/96ja00684
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration and heating of heavy ions by circularly polarized Alfvén waves

Abstract: We study the dispersion relation of left‐hand‐polarized Alfvén waves in multicomponent plasmas. If initially the plasma components are not drifting relative to each other, the Alfvén waves propagate until they meet the gyrofrequency of the species with the largest Ml = ml/zlmp value (ml is the ion mass, zl is the degree of ionization, and mp is the proton mass). As a result of resonance absorption, these ions are heated and accelerated by quasi‐linear resonant interaction. When these ions reach a given velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 10 publications
5
36
0
Order By: Relevance
“…In past the studies on EMIC instability, including H + e , O + and their anisotropies, have been performed by various authors (Gomberoff and Neira, Published by Copernicus GmbH on behalf of the European Geosciences Union. 558 G. Ahirwar et al: Beam effect on electromagnetic ion-cyclotron waves 1983; Gomberoff and Elgueta, 1991;Gomberoff et al, 1996;Thorne and Horne, 1997;Horne and Thorne, 1997). In the present analysis, we have considered only H + e to examine the behavior of EMIC waves for the auroral acceleration process.…”
Section: Introductionmentioning
confidence: 99%
“…In past the studies on EMIC instability, including H + e , O + and their anisotropies, have been performed by various authors (Gomberoff and Neira, Published by Copernicus GmbH on behalf of the European Geosciences Union. 558 G. Ahirwar et al: Beam effect on electromagnetic ion-cyclotron waves 1983; Gomberoff and Elgueta, 1991;Gomberoff et al, 1996;Thorne and Horne, 1997;Horne and Thorne, 1997). In the present analysis, we have considered only H + e to examine the behavior of EMIC waves for the auroral acceleration process.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of nonzero drift ) p speeds between ions also a †ects the dispersion relation (see below), but here is assumed for simplicity. Note that u p \ u a in the warm plasma case, only the lower frequency branch in Figure 4 (solid line) connects to the limit of dispersionless MHD waves, and it is thought that most outward Alfve n propagating waves in the corona will tend to populate this branch (e.g., Gombero †, Gratton, & Gnavi 1996). Figure 4 also displays solutions for the damping rate c. In the cold plasma branch, the quasi-linear relations in equations (12), (13), (14), and (15) were used for protons and alphas ; in the warm plasma branches, the complex dispersion relation was solved numerically for u and c simultaneously (e.g., Stix 1962 ;Isenberg 1984a ;.…”
Section: Figmentioning
confidence: 99%
“…In the cold-plasma limit, each ion speciesÈno matter how low its abundanceÈgenerates its own solution branch. Such an unphysical situation is remedied by the inclusion of warm plasma e †ects that smooth over many of these branches and probably allow Alfve n waves to propagate for all frequencies below the more robust asymptote (e.g., Gombero † et al 1996 ; Gom-) a bero † & Astudillo 1999 ;Hu 1999). Also, the presence of nonzero drift speeds between ions has the ability to eliminate dispersion branches of low-abundance species.…”
Section: Figmentioning
confidence: 99%
“…More recently, Gomberoff et al [1996aGomberoff et al [ , 1996b pointed out the possible role played by gaps in the multi-ion dispersion relation in the preferential heating of helium and other minor ions. They suggested that since most of the wave energy resides on the lowest frequency branch, heating and acceleration of ions with the lowest charge to mass ratio must occur until distortion of the distribution functions is sufficient to change the dispersion relation enough for modes of higher frequency to arise.…”
Section: Introductionmentioning
confidence: 99%